1. The problem statement, all variables and given/known data Hello! One of the easiest rules (when possible to apply) to factor a quadratic is to find both x-s by x1 + x2 = b x1 * x2 = c 2. Relevant equations Please, take a look at what is written in the book. I can't grasp why x1 = -2 and x2 = 3, and not, as I thought, x1 = -3 and x2 = 2. 3. The attempt at a solution What is wrong in my understanding? x1 + x2 = -1 x1 * x2 = -6 Therefore, x1 = -3 and x2 = 2; and the equation (x + 3 )(x - 2) =0 I would be grateful for the help. Thank you!